A Systematic Review on Nexus Between Green Finance and Climate Change: Evidence from China and India - Shah, Shangram Bahadur; Sopin, Jirakiattikul; Techato , Kua-Anan; Mudbhari, Bibek Kumar (International Journal of Energy Economics and Policy, 2023)
The efforts of developing economies are mainly concerned with integrating different socio-economic requirements. In contrast, those economies only concentrate on the immediate impact to be resolved instead of focusing on efforts to mitigate long-run effects such as climate change: a global challenge due to long-term shifts in weather and temperature pattern. Climate change has resulted in global warming, severe storms, and increased droughts, including risks to human health, loss of biodiversity, poverty, and displacement, whereby green finance is considered a primary solution to mitigate such problems that can ensure sustainable environmental outcomes while promoting the agenda of, decarbonization, green tech innovation, green financial innovation, and green growth. This systematic review paper studies the nexus between green finance and climate change in China and India. This article follows Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines and reviews Scopus and Web of Science indexed peer-reviewed articles of five years published from 2018 AD to 2022 AD and 58 full-text articles were reviewed. The paper’s significant findings reveal that innovation in finance and technology are the major frontiers of green financing that are critical in addressing the problems of climate change. It is environmental regulations that accentuate the process of green financial innovation and green technology innovation. However, green financial innovation is also a catalyst for green technology innovation. Green financial innovations are related to developing and innovating green financial products such as green bonds or loans, green insurance or securities, ESG rating, perception of environmental issues, and carbon drifting. On the other hand, green tech innovations are innovations in energy, transport, construction, and buildings. Innovations in technology and finance backed by environmental regulations strengthen the effort toward decarbonization. Regulatory interventions in green financing have more pronounced effects on emission reduction. Such actions are oriented towards green growth where the desired sustainable outcomes are realized regarding climate change adaptation, mitigation, or carbon neutrality.